The role of legal responsibility in the implementation of the principle of the unity of public authority in Russia - A. V. Malko; D. A. Lipinsky; R. S. Markunin (Правоприменение)
The subject. The article presents a comprehensive general theoretical analysis of the institution of legal responsibility and its role, taking into account the consolidation of the new constitutional and legal principle of the unity of the system of public power.The purpose of the research is to confirm or disprove hypothesis that it is necessary to legislate a full-fledged mechanism of legal responsibility of state bodies and local self-government bodies in order to implement the constitutional principle of the unity of public power.Methodology. The formal legal method, the method of comparative legal analysis, dialectical method and systemic approach were used.The main results, scope of application. The authors found the manifestation of dualism in the work of the institution of legal responsibility. It consists in the ability to bear responsibility both to the state, in connection with various offenses, and to the population itself. A brief description of the loss of trust as a basis for the responsibility of officials is given, taking into account contemporary legislation. Directions for the further development of this legal institution are highlighted. The article examines the opinion of the Russian Constitutional Court on the legitimacy of using the loss of trust as a basis for the responsibility of public authorities. The article examines the normative legal acts, which fix the mechanism for the implementation of the principle of maintaining trust in the activities of the authorities on the part of society. For example, in relation to state civil and municipal employees, a prohibition has been established on statements about the activities of authorities and their assessment, if such actions are not included in the list of their official duties. Such a mechanism for maintaining public confidence in the work of government bodies should contribute to strengthening the unity of the public power system. At the same time we can talk about the existing trend towards a decrease in the level of public confidence in the work of authorized bodies exercising public authority. The corruption and bureaucratization of the activities of officials, the expansion of the powers of law enforcement agencies, a decrease in the independence of the political opposition are pointed to among the possible reasons most often. In this regard, the paper proposes expanding the grounds for responsibility when implementing the procedure for recalling an official.Conclusions. It is necessary to consolidate a full-fledged legislative mechanism of legal responsibility of state bodies and local self-government bodies, which will contribute to the implementation and strengthening of the new principle of the unity of public authority.